Minimally-invasive bedside catheter haematoma aspiration followed by local thrombolysis in spontaneous supratentorial intracerebral haemorrhage: a retrospective single-center study - Hieber, Maren; Lambeck, Johann; Halaby, Amjad; Roelz, Roland; Demerath, Theo; Niesen, Wolf-Dirk; Bardutzky, Jürgen (Frontiers in Neurology, 2023)
Background and purpose The role of surgery in the treatment of intracerebral haemorrhage (ICH) remains controversial. Whereas open surgery has failed to show any clinical benefit, recent studies have suggested that minimal invasive procedures can indeed be beneficial, especially when they are applied at an early time point. This retrospective study therefore evaluated the feasibility of a free-hand bedside catheter technique with subsequent local lysis for early haematoma evacuation in patients with spontaneous supratentorial ICH. Methods Patients with spontaneous supratentorial haemorrhage of a volume of >30 mL who were treated with bedside catheter haematoma evacuation were identified from our institutional database. The entry point and evacuation trajectory of the catheter were based on a 3D-reconstructed CT scan. The catheter was inserted bedside into the core of the haematoma, and urokinase (5,000 IE) was administered every 6 h for a maximum of 4 days. Evolution of haematoma volume, perihaemorrhagic edema, midline-shift, adverse events and functional outcome were analyzed. Results A total of 110 patients with a median initial haematoma volume of 60.6 mL were analyzed. Haematoma volume decreased to 46.1 mL immediately after catheter placement and initial aspiration (with a median time to treatment of 9 h after ictus), and to 21.0 mL at the end of urokinase treatment. Perihaemorrhagic edema decreased significantly from 45.0 mL to 38.9 mL and midline-shift from 6.0 mm to 2.0 mm. The median NIHSS score improved from 18 on admission to 10 at discharge, and the median mRS at discharge was 4; the latter was even lower in patients who reached a target volume ≤ 15 mL at the end of local lysis. The in-hospital mortality rate was 8.2%, and catheter/local lysis-associated complications occurred in 5.5% of patients. Conclusion Bedside catheter aspiration with subsequent urokinase irrigation is a safe and feasible procedure for treating spontaneous supratentorial ICH, and can immediately reduce the mass effects of haemorrhage. Additional controlled studies that assess the long-term outcome and generalizability of our findings are therefore warranted. Clinical trial registration [www.drks.de], identifier [DRKS00007908].